Research Progress on Phage Diversity, Auxiliary Metabolic Functions and Host Interactions in Fermented Foods - QI Shaohan, TAN Guiliang, CHEN Sui, LI Xiangli, LI Lin, ZHAO Lichao, DONG Xiutao (Shipin Kexue)
Phages are the most diverse and abundant biological entities on earth. In recent years, the proliferation of high-throughput sequencing technology has led to a surge in research on the composition and functions of phages in diverse ecological niches. Particularly, phages in fermented foods have been receiving increasing attention from researchers, which interact with their bacterial hosts through the lytic and lysogenic life cycles, playing important ecological roles and influencing the succession of microbial communities. Additionally, phages also exhibit potential auxiliary metabolic functions, which in turn affects the formation of flavor substances in fermented foods to a certain extent. This paper provides a comprehensive review of the present status and hot topics of research on phages in fermented foods, with a specific focus on the composition, diversity, genomic DNA extraction techniques and auxiliary metabolic functions of phages as well as their interactions with the host and the underlying mechanism (e.g., clustered regularly interspaced short palindromic repeats (CRISPR) and binding receptors). Finally, this review concludes with a discussion of future research directions, aiming to provide a reference for further research and application of phages in fermented foods.